2014
DOI: 10.4172/2329-6674.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Purification and Characterization of Secondary Structure and Kinetic Study of Lipase from Indian Major Carp, Catla catla (Catla)

Abstract: Lipases are ubiquitous enzymes which catalyze the hydrolysis of fats into fatty acids and glycerol at the waterlipid interface and reversing the reaction in non-aqueous media. Lipases occupy a place of prominence among biocatalysts owing to their novel and multifold applications in oleochemistry, organic synthesis, detergent formulation and nutrition. Lipase was extracted and isolated from the alimentary canal and digestive gut of Catla catla (catla). The tissue was homogenized in a ratio of 1:3 with starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…K m and V max were calculated using the Lineweaver-Burk plot and Michaelis-Menten equation. The turnover rate (k cat ) and the catalytic efficiency of ZZ-YLIP9 were calculated using the following formulae [12]:…”
Section: Kinetic Parameters Of Zz-ylip9mentioning
confidence: 99%
“…K m and V max were calculated using the Lineweaver-Burk plot and Michaelis-Menten equation. The turnover rate (k cat ) and the catalytic efficiency of ZZ-YLIP9 were calculated using the following formulae [12]:…”
Section: Kinetic Parameters Of Zz-ylip9mentioning
confidence: 99%
“…SDS-PAGE and zymography analysis forecasted the expected molecular mass of lipase was about 32 kDa (Figures 1.A and 1.B). This finding was supported by Sharma et al (2014) who characterized lipase from the alimentary canal and digestive gut of Catla catla (catla) with 30 and 67 kDa in dialysate fraction of SDS-PAGE. Similarly, Kurtovic et al (2009) reported that a partially purified lipase from the hepatopancreas of neo flying squid (Ommastrephes bartramii) showed a molecular weight of 33 kDa, lower compared to the pancreatic lipase from mammalian species.…”
Section: Purification Of Protease and Lipasementioning
confidence: 60%